Genetic linkage map construction and QTL mapping of blade length and width in Saccharina japonica using SSR and SNP markers - Wang, Xiuliang; Yang, Xiaoqi; Yao, Jianting; Li, Qiuying; Lu, Chang; Duan, Delin (Frontiers in Marine Science, 2023)
MAS (marker assisted selection) is useful for cultivar development in the lower plant Saccharina japonica. In this study, 167 screened SSR markers and 125 individuals were used to construct a S.japonica genetic linkage map with 27 linkage groups and a total Haldane length of 2069 cM. Constructed linkage groups were aligned with assembled pseudo-chromosomes of S. japonica genome sequences (NCBI: MEHQ00000000) and anchored to 23 of 31 pseudo-chromosomes. A genetic linkage map including 33 linkage groups was constructed with combined 3397 SSR and SNP markers. In the integrated genetic map used for QTL mapping, SSR marker M1895 was closely associated with the major QTL for blade length and width with LOD threshold of >5.0. Annotation indicated that SjPT, coded as a high affinity phosphate transporter, was mapped to this major QTL with cDNA sequence of 1422 bp, which coded 473 aa for 8 transmembrane helics. qRT-PCR and the transcriptomic detection confirmed that SjPT transcription was consistent with increases in kelp blade length and width. Marker M1895 appears to be particularly useful for MAS (marker assisted selection) in S. japonica breeding.